2010
DOI: 10.1159/000260417
|View full text |Cite
|
Sign up to set email alerts
|

The Toll-Like Receptor 4 D299G and T399I Polymorphisms Are Associated with Crohn’s Disease and Ulcerative Colitis: A Meta-Analysis

Abstract: Background: Some studies have reported that Toll-like receptor 4 (TLR4) D299G and T399I polymorphisms are associated with increased Crohn’s disease (CD) and ulcerative colitis (UC) risk in the Caucasian population. However, the results have been inconsistent. Methods: A systemic review of the published data (16 studies with 8,387 cases and 7,013 controls for D299G; 8 studies with 3,881 cases and 1,861 controls for T399I) was undertaken and a meta-analysis was performed to test whether TLR4 D299G and T399I poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 87 publications
1
43
1
2
Order By: Relevance
“…Contrary to meta-analysis reported by Shen et al [39], our current study suggested that the TLR4 T399I polymorphism might not be associated with CD susceptibility in Caucasians, while moderate association was observed in Asians. Some differences exist between our analysis and other meta-analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to meta-analysis reported by Shen et al [39], our current study suggested that the TLR4 T399I polymorphism might not be associated with CD susceptibility in Caucasians, while moderate association was observed in Asians. Some differences exist between our analysis and other meta-analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…8,9 Moreover, a meta-analysis revealed that genetic variations in TLR4 conferred a statistically significant risk of developing CD and UC. 10 In addition to TLR4, polymorphisms in TLR2, the main receptor for gram-positive bacteria, have been associated with IBD in humans and there is an inflammation-dependent induction of TLR2 expression in intestinal macrophages. 11,12 On activation of the TLRs, different adaptor proteins, including MyD88, Mal (TIRAP), TRIF (TICAM), TRAM, (TICAM2), or SARM are recruited, and they trigger a signaling pathway, leading to the subsequent downstream activation of signals such as transcription factor NF-jB (nuclear factor-jB), which are responsible for induction of pro-inflammatory cytokines and chemokines.…”
mentioning
confidence: 99%
“…Previous meta-analysis indicated that TLR4 polymorphisms appeared to be correlated with Crohn's disease, ulcerative colitis [8], vasculitis [9] and cancer [10], but not with sepsis [11], rheumatoid arthritis, ankylosing spondylitis [12][13][14], and atherosclerosis [15]. In the present study, we performed a systematic review of the association between TLR4 Asp299Gly and Thr399Ile polymorphisms and the risk of ADs.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, in previous meta-analyses TLR4 polymorphisms appeared to be correlated with Crohn's disease, ulcerative colitis [8], vasculitis [9] and cancer [10], but not with sepsis [11], rheumatoid arthritis, ankylosing spondylitis [12][13][14], and atherosclerosis [15]. To date, a number of molecular epidemiological studies have been done to evaluate the association between TLR4 Asp299Gly and Thr399Ile polymorphisms and several autoimmune diseases (ADs) including type 1 diabetes (T1DM) [16], celiac disease (CED) [16, DOI: 10.5114/ceji.2013.37757 17], rheumatoid arthritis (RA) [18][19][20][21], multiple sclerosis (MS) [22,23], and systemic lupus erythematosus (SLE) [19] in Caucasians.…”
Section: Introductionmentioning
confidence: 95%